Penerapan Sistem Pelaporan Keuangan Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu, Tenaga Kerja dan Transmigrasi Aceh Barat Daya - Yusrina Dewi; Dewi Sartika (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2022)
The reason for this research is to find out the application of the Financial Information System at the Office of Investment and One Stop Service, Manpower and Transmigration (DPMPTSP) Aceh Barat Daya Regency. The type of research used in this research is descriptive qualitative research which is carried out to describe the research subject based on events that occur or what they are. Data was collected through observation and interviews as well as data collection in accounting reporting information management procedures. As well as agency data in the form of agency descriptions. The results of the study conclude that the Office of Investment and One Stop Integrated Services, Manpower and Transmigration of Southwest Aceh Regency in general has established an accounting reporting system in accordance with Government Regulation Number 71 of 2010 concerning Accrual Accounting Standards.